The Impact of Modifying the Junior Volleyball Dimensions Court and the Related Equipment By Applying the Concept of Human Engineering Ergonomics on the Skill Performance in Volleyball - Mwafaq Abu Ahmada; Abdelsalam Hussain (Sultan Qaboos University, 2013)
The purpose of the study was to investigate the impact of modifying the dimensions of junior volleyball court and the related equipment on the skill performance in volleyball by applying the concept of human engineering ergonomics. A purposive sample of 40 male students at Al-Frair basic school was selected. The sample was divided into two groups: experimental group (20) and control group (20). The two groups implemented the suggested learning program with the experimental used the modified volleyball playground, while the control group used ordinary volleyball playground. The learning program lasted 8 weeks /3 learning sessions per week and that each learning unit lasted 45 minutes. The results showed that the performance of the experimental group was enhanced significantly compared to the control group in the post test, suggesting the impact of ergonomics in modifying the volleyball play-ground dimensions and the related equipment. The researchers recommend utilizing the modified playground as it reflects significant related skill performance for (8-10) years aged students and to apply the concept of ergonomics in the different PE sciences to modify both dimensions and the related equipment to go with the relevant age group.